A virtual manufacturing workcell for automated assembly - Sato, Akihiro, author; Maciejewski, Anthony A., author; Autosoft® Press, publisher (Colorado State University. Libraries, 1996)
This work describes the implementation of a novel robot workcell programming interface that allows an assembly designer to obtain immediate feedback regarding the manufacturability of his/her design. The interface allows the user to manipulate the three-dimensional CAD/CAM models of the components and "assemble" them into the final product. The computer then analyzes the relevant assembly operations and translates them into low-level commands for the robots in the specific workcell under consideration. This work is motivated by the complexity and time-consuming nature of manually programming flexible assembly cells for the manufacture of different products, particularly when they involve the cooperation of multiple robot manipulators.
Keywords: virtual environment; automated assembly